STRATIGRAPHY ANALYSIS AND SEISMIC FACIES IDENTIFICATION ON SYN-RIFT INTERVAL, KOTAGARO FIELD, CENTRAL SUMATRA BASIN - Oryzavica Vebryatna, Vicco
The Kotagaro area is one of the areas that has a hydrocarbon field in the Central Sumatra basin. The Central Sumatra Basin itself is one of the old basins that have produced a lot of hydrocarbons in Indonesia. In its development, the field in the Kotagaro area only explores post-rift deposit. Synrift deposit Pematang Group is still not explored to be used as a reservoir. Research on synift interval in the study area have not been explored further because they are not a focus study. Research on synrift interval is expected to be able to become new knowledge, especially in the Kotagaro area. This study aims to explore new insights regarding synrift interval by analyzing seismic facies and interpreting the depositional environment of the study area. The study used 2D and 3D seismic data and one well data outside the study area. Well data is used only for well-seismic tie. The methods used in this study include well-seismic tie, 2D and 3D seismic interpretations on intervals of sediment packages during synrift, making time structure maps and isochrone maps, seismic facies analysis, and interpretation of depositional environments. Based on theses analysis, the study area has a northwest-southeast trending which is resulting from an extensional ENE-WSW tectonic regime. The results of seismic analysis show that the research area has four seismic facies, facies AM, DM, HM, and PM. The four seismic facies showed that the study area was deposited in the fluvial zone, alluvial fan zone, deep lacustrine zone, shallow lacustrine zone, and lacustrine shoreline zone.